ANALISIS PENGARUH KEPEMIMPINAN BERBASIS TEKNOLOGI TERHADAP PENINGKATAN KINERJA PEGAWAI DI PUSKESMAS MATARAM - Khaeri, Anas; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu; Fathurrahman (Nusadaya Journal of Multidiciplinary Studies, 2024)
Respondents in this study were predominantly female (63.08%), while males comprised 36.29%. This dominance may reflect the actual population of employees at the Mataram Community Health Center, or indicate that women tend to be more active in survey participation. Despite the disparity in proportions, the representation of both genders still contributes to the diversity of data that supports the objectivity of the analysis. The majority of respondents were in the productive age category (25–44 years), at 78.46%. This age group is considered to be in a socially and economically active period, and generally has understanding and work experience relevant to the research topic. Meanwhile, participation from the age groups under 25 and over 54 was relatively low, which could be due to the limited number or involvement in survey activities. The composition of positions shows that health workers such as midwives and nurses dominate the number of employees, indicating their central role in Community Health Center services. The proportion between civil servants and non-civil servants is relatively balanced for core positions, but strategic or specialist positions are still dominated by civil servants. Meanwhile, non-health positions tend to be filled more by non-civil servants. This shows a fairly clear division of labor between technical and administrative roles.